Personality Development Among Contemporary Nigerian Youths: Psychoanalytic, Social Learning and Islamic Perspectives - Musa Adebayo, Badrudeen (Al-Basirah Journal, 2025)
Personality as a behavioural make up and attitudinal uniqueness of every individual serves as means of distinguishing one person from others. As psychoanalysis theorists perceive behavioural manifestation majorly as a result of unconsciousness, heredity and early childhood experiences, social learning theorists on the other hand understand it as a result of consciousness and external influences. Youths, like other human beings do manifest different kinds of desirable and undesirable characters under the influences of both intrinsic and extrinsic stimuli. Majority of the contemporary Nigerian youths also manifest both moral and immoral behaviours. Therefore, this paper aims at uncovering the degrees of influences of both the psychoanalysis and social learning factors on the personality of contemporary youths. The paper also discusses the Islamic psychological position on personality development of the youths. Descriptive and analytical research methods were used in this work. The paper explains the ideal Islamic all-round personality development and also analyses behavioural modification using the Qur’ān, Sunnah and views of the Islamic scholars. The research findings reveal that both the psychoanalysis and social learning factors have significant influences on every individual personality. The paper, therefore, concludes by encouraging the parents, teachers and other stake holders to train the children in line with the Islamic laid down child upbringing teachings.